Historical Analysis on Tropical Fruit Production at Coastal Sandy Farming Land in Rural Yogyakarta, Indonesia - ., Subejo; Mewasdinta, G (KnE Life Sciences, 2019)
As one of the autonomic district in Yogyakarta Special Region, Kulon Progo district has a huge of coastal sandy farming lands. In general, coastal sandy farming land in Kulon Progo has been widely acknowledged as common resources that the resource acess formally is owned and managed by Pakualam Ground. Various efforts in coastal sandy farming land are undertaken for improving income of coastal communities. Thanks to initiative actions of particular farmer leaders, marginal land in coastal area can be converted more productive land for agricultural production. Currently, several tropical fruits such as watermelon [Citrullus lanatus (Thunb.) Matsum. & Nakai] and papaya (Carica papaya L.) can be produced in coastal sandy land as a newly developed area. The research was conducted in Panjatan District Kulon Progo Regency in order to determine historical aspects of access and utilization of coastal sandy farming land. The method used in this research was descriptive-analytic. The research results showed that historically access and utilization of coastal sandy farming land included the support of consolidation scheme of land plot arrangement incoastal sandy farming area. Community members which have been initiated by group leaders have arranged the division and allocation of coastal land for each farmer. The coastal farming land can be utilized by farmers for cultivation and farm roads building for supporting the crops production. The process has been done during 1996 to 1999. After getting coastal farming plot, farmers could manage farming land and improve the agricultural production dramatically. Keywords: Coastal, Land consolidation, Sandy farming, Tropical fruit, Yogyakarta